Viral-associated septic shock in pediatric pneumonia: a retrospective analysis of pathogen-specific risks and comparative clinical features with bacterial sepsis - Cheng, Ying; Chen, Kun; Qian, Hui-ling; Hu, Hong-bo (Frontiers in Pediatrics, 2025)
BackgroundThis study aimed to determine the incidence of septic shock in hospitalized children with viral pneumonia, identify high-risk viral pathogens, and compare the clinical features between viral- and bacterial-associated septic shock cases.MethodsA retrospective study on viral respiratory infections in children hospitalized with pneumonia at two hospitals between 2022 and 2024 was conducted, with logistic regression used to assess the pathogen-specific risks.ResultsAmong 5,956 children with viral pneumonia, the incidence of septic shock was 1.06%, varying significantly by pathogen (p < 0.001). Influenza A (FluA) showed the highest incidence (3.70%) and was the strongest predictor of shock [odds ratio (OR) = 7.506], followed by respiratory syncytial virus (RSV) (2.24%; OR = 4.559). Compared to bacterial shock cases (n = 46), viral shock cases showed higher respiratory failure/acute respiratory distress syndrome (ARDS) rates (88.9% vs. 52.2%, p < 0.001) but they had shorter hospital stays (17.3 vs. 24.2 days, p = 0.026). FluA cases were more likely to have less infant involvement (p = 0.023), more neurologic compromise (35.7% vs. 8.7%, p = 0.040), and develop refractory shock (42.9% vs. 8.7%, p = 0.007) compared to bacterial cases. RSV showed higher respiratory failure (75.9% vs. 52.2%, p = 0.040) and lower coagulopathy (34.5% vs. 60.9%, p = 0.026) rates.ConclusionsFluA and RSV are the key viral pathogens that predispose pediatric pneumonia patients to septic shock. Rapid viral polymerase chain reaction testing enables early pathogen identification, facilitating antibiotic de-escalation when bacterial coinfection is unlikely and promoting precise, safe antimicrobial stewardship.